2020
DOI: 10.1111/ppa.13151
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, plant growth‐promoting traits, and biocontrol potential of fungal endophytes of Sorghum bicolor

Abstract: The diversity of fungal endophytes in Sorghum bicolor was investigated in samples collected from 10 different geographical regions of Karnataka state, India. A total of 360 endophytes were isolated from leaf, stem, and root tissues and were assigned to 26 fungal species based on morphology and molecular characterization using ITS sequences. All the endophytes belonged to the phylum Ascomycota. The diversity (Shannon H, 2.57; Simpson_1‐D, 0.92) and species richness (Margalef's, 4.68; Menhinick, 3.61) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Similarly, many researchers have used the same method in order to isolate endophytic fungi from many medicinally important plants . [41][42][43][44]17,7 Further, all the isolates were evaluated for their antagonistic nature against the early blight pathogen A. solani by the dual culture method. From the results, it was noted that only five endophytic fungi revealed against the test pathogen with a maximum inhibition of 58.33% offered by P. microspora.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, many researchers have used the same method in order to isolate endophytic fungi from many medicinally important plants . [41][42][43][44]17,7 Further, all the isolates were evaluated for their antagonistic nature against the early blight pathogen A. solani by the dual culture method. From the results, it was noted that only five endophytic fungi revealed against the test pathogen with a maximum inhibition of 58.33% offered by P. microspora.…”
Section: Discussionmentioning
confidence: 99%
“…In corroboration with the findings of the study, seed treatment with conidial suspension of endophytic fungi isolated from medicinal plants was able to enhance seed germination, seedling vigor, vegetative and reproductive plant growth parameters in sorghum and turmeric plants. 14,7 The beneficial nature towards the enhancement in seed, vegetative and reproductive plant growth parameters from microbial endophytes is mainly correlated to the production of plant hormones and antimicrobial compounds, therefore, helping the plants in nutritional improvement which positively impacts plant growth. 49,50,17,15 In addition to plant growth-promoting studies, the application of fungal endophytic seed treatment was also able to induce disease resistance against the early blight pathogen in tomato.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While similar systemic effects have not been shown in sorghum, a trend such as this would result in increased host favoritism of the many components of the flavonoid pathway that are related to SGM resistance, hypothetically resulting in increased SGM resistance at a potential cost of yield due to a change in photosynthate partitioning. While few endophyte-related host systemic changes have been shown in relation to sorghum host resistances, localized biocontrol of SGM pathogens by fungal endophytes has been demonstrated (Rajini et al, 2020). Rajini et al (2020) showed biocontrol effects were demonstrated by 26 endophytic isolates on common SGM complex pathogens: Fusarium thapsinum, Epicoccum sorghinum, Alternaria alternata, and Curvularia lunata.…”
Section: Moving Forward With Elucidating Sgm Host-pathogens Interactions and Developing Sgm Resistant Cultivarsmentioning
confidence: 99%